Effect of Change in Iris Color on Myopia - Faisal Rashid, Maryam Jabbar, Naseer Fatima, Muhammad Siddique, Asia Hussain, Khalid Waheed, (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The purpose of this study was to determine the distribution of iris colour and its relationship to myopia. Methods: A multi-centered, multi-disciplined, cross-sessional study was conducted From March 2021 to December 2021. 300 individuals ranging in age from 11 to 25 years were selected through non-probability purposive sampling technique. All the patients had a maximum of 6 hours of screen time. Mild, moderate and severe degree of myopia was included. All subjects were examined for refraction, and slit lamp examination was performed to compare slit lamp photos to an iris colour grading scheme. Results: Of the 300 subjects 188 (62.66 %) of the participants were female, with mild 70(23 %), moderate 51(17%), and severe 67 (22.33 %) myopia, while 112 (37.33 %) of the participants were male, with mild 45(15 %), moderate 40(13.33%), and severe 27(9 %) myopia. 90% of the participants in the study had Grade 3, 4 and 5 iris color.Subjects with darker iris colors had more myopic refractive error. Study results indicate patients with Grade 5 iris color had a higher likelihood of becoming myopic (p 0.001). Conclusion: Darker iris color was linked to higher myopia-related refractive errors, even when other known myopia-related risk variables were taken into account.